2012
DOI: 10.1111/ctr.12014
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of non‐alcoholic steatohepatitis and cryptogenic cirrhosis following orthotopic liver transplantation in the context of the metabolic syndrome

Abstract: Higher recurrence of NASH and CC was associated with presence of MS, HTN and insulin use. Recurrence should be further evaluated in larger studies, with special emphasis on management of MS and prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 30 publications
0
58
0
1
Order By: Relevance
“…Although these noninvasive methods can detect hepatic steatosis, but the recurrence of NASH could not be assessed. Metabolic syndrome, including obesity and type 2 diabetes mellitus, plays an essential role in the recurrence of NASH after LT (El Atrache et al 2012). Recurrence of NASH has not been observed in patients with significantly reduced weight after LT (Koneru and Dikdan 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although these noninvasive methods can detect hepatic steatosis, but the recurrence of NASH could not be assessed. Metabolic syndrome, including obesity and type 2 diabetes mellitus, plays an essential role in the recurrence of NASH after LT (El Atrache et al 2012). Recurrence of NASH has not been observed in patients with significantly reduced weight after LT (Koneru and Dikdan 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Contos et al, 9 Ong et al, 10 El Atrache et al, 19 and Dureja et al 20 found advanced fibrosis, greater than grade 3, in about 4% of the samples. Contos et al 9 associate the increased recurrence of NAFLD with the use of corticosteroids.…”
Section: Recurrence Of Nash and De Novo Nashmentioning
confidence: 94%
“…The authors observed that patients transplanted due to NASH have an incidence of MetS similar to those transplanted for other reasons, around 50% (Table 3). In the series evaluated by Laish et al 35 and El Atrache et al, 19 the population evaluated consisted exclusively of patients transplanted due to NASH. In the investigation by Seo et al, 40 the population consisted of patients with de novo NASH.…”
Section: Recurrence Of Nash and De Novo Nashmentioning
confidence: 99%
See 2 more Smart Citations